PENGEMBANGAN BUKU AYO MENJELAJAHI SISTEM PENCERNAANKU BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Chaerunnisa; Syawaluddin, Ahmad; Irfan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and analyze the feasibility, practicality, and effectiveness of augmented reality-assisted teaching materials for the high grade at SDI Pajjaiang. This type of research is research and development (R&D) using a developmental research approach with the ADDIE model. The data obtained consists of qualitative data and quantitative data. This study involved one fifth-grade teacher, ten sixth-grade students in a small-group trial, and twenty-five fifth-grade students in a large-group trial. The research results show that: (1) this research produced the book "Ayo Menjelajahi Sistem Pencernaanku", which is a teaching material assisted by augmented reality for science material about the human digestive system; (2) the feasibility analysis based on expert validation was  in the very feasible category, and the material expert validation was in the very feasible category; (3) the practicality analysis based on the results of the teacher respondent questionnaire was in the very practical category and the results of the student respondent questionnaire in the small group and large group trials were in the practical category; (4) the effectiveness analysis based on the results of the post-test of students with classical completeness was in the good category and from the N-Gain calculation of the pre-test and post-test scores was in the high category. It can be concluded that student learning outcomes in high-grade science subjects at SDI Pajjaiang can be improved by using augmented reality-assisted teaching materials.